2018
DOI: 10.1007/s00117-018-0404-6
|View full text |Cite
|
Sign up to set email alerts
|

CEUS – Einsatzmöglichkeiten am Bewegungsapparat

Abstract: CEUS of the musculoskeletal system is used in clinical trials or off-label. Therefore, it is not well established in clinical routine. However, considering the increasing number of musculoskeletal CEUS applications, this could change in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 70 publications
0
2
0
1
Order By: Relevance
“…Außerhalb der Oberbauchorgane gibt es ebenfalls Anwendungsmöglichkeiten für CEUS, beispielsweise an der Skelettmuskulatur zur Visualisierung und Quantifizierung der Mikroperfusion [7]. Eine innovative Anwendungsmöglichkeit des CEUS zeigen die Arbeiten von Fischer [10].…”
Section: Kontrastverstärkter Ultraschall (Ceus)unclassified
“…Außerhalb der Oberbauchorgane gibt es ebenfalls Anwendungsmöglichkeiten für CEUS, beispielsweise an der Skelettmuskulatur zur Visualisierung und Quantifizierung der Mikroperfusion [7]. Eine innovative Anwendungsmöglichkeit des CEUS zeigen die Arbeiten von Fischer [10].…”
Section: Kontrastverstärkter Ultraschall (Ceus)unclassified
“…Contrast-enhanced ultrasound (CEUS) can display the tumor microvessel in real time with almost no side effects and a wide range of applications (10,11). The relationship between tumor microvascular angiogenesis regulated by vascular endothelial growth factor (VEGF) and Ki-67 LI has been confirmed in previous research (12).…”
Section: Introductionmentioning
confidence: 99%
“…It is easily accessible, cost-efficient, and quick to use [ 9 ]. Furthermore, the used ultrasound contrast agent SonoVue © (Bracco Imaging, Milan, Italy) has a low complication rate [ 10 , 12 ] and CEUS offers real-time examination in the contrast dynamics of the inspected tissues [ 9 ]. In a recent study, CEUS has been shown to be effective in monitoring the vascularity of non-unions [ 9 ] and distinguishing preoperatively based on the microperfusion between infected and non-infected non-unions [ 9 ].…”
Section: Introductionmentioning
confidence: 99%